Body Failure : Medical Views of Women, 1900-1950 - Mitchinson, Wendy (Book collections on Project MUSE., 2013)
In this energetic new study, Wendy Mitchinson traces medical perspectives on the treatment of women in Canada in the first half of the twentieth century.